Антиоксидантно-прооксидантний баланс внутрішніх органів і цитокіновий статус у динаміці політравми в експерименті = Antioxidant-prooxidant balance of the internal organs and cytokine status in the experiment polytrauma - D. V. Kozak (Kazimierz Wielki University, 2015)
Kozak D. Антиоксидантно-прооксидантний баланс внутрішніх органів і цитокіновий статус у динаміці політравми в експерименті = Antioxidant-prooxidant balance of the internal organs and cytokine status in the experiment polytrauma. Journal of Education, Health and Sport. 2015;5(8):507-520. ISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.32162 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%288%29%3A507-520 https://pbn.nauka.gov.pl/works/657188 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 26.07.2015. Revised 05.08.2015. Accepted: 24.08.2015.   УДК 616.1/9-092.19-097-02:616-001.3/6]-092.9   АНТИОКСИДАНТНО-ПРООКСИДАНТНИЙ БАЛАНС ВНУТРІШНІХ ОРГАНІВ І ЦИТОКІНОВИЙ СТАТУС У ДИНАМІЦІ ПОЛІТРАВМИ В ЕКСПЕРИМЕНТІ ANTIOXIDANT-PROOXIDANT BALANCE OF THE INTERNAL ORGANS AND CYTOKINE STATUS IN THE EXPERIMENT POLYTRAUMA   Д.В. Козак D. Kozak   Державний вищий навчальний заклад "Тернопільський державний медичний університет імені І. Я. Горбачевського МОЗ України" State Higher Educational Establishment "I. Horbachevsky Ternopil State Medical University of the Ministry of Public Health of Ukraine"   Summary The results of research content of pro- and anti-inflammatory cytokines in serum and antioxidant-prooxidant balance of heart tissue, lung and liver in the dynamics of the acute period, the early and late manifestations of traumatic disease (within 28 days) after causing trauma. Found that the post-traumatic period, an increase in pro-inflammatory cytokines content. Defining feature of tumor necrosis factor-α and interleukin-1b were two periods of maximum growth - at 3 and 21 days. Antioxidant-prooxidant balance in the tissue of the heart, lungs and liver in all periods of observation was shifted towards predominance of oxidative mechanisms characterized by the same two periods of major violations: after 3 and 21 days. The results suggest that the dynamics of trauma exists matching the largest manifestations of systemic inflammatory response of the body to the maximum intensification of lipid peroxidation in internal organs. Key words: polytrauma, cytokines, antioxidant-prooxidant balance.   Резюме У статті наведено результати досліджень вмісту про- і протизапальних цитокінів у сироватці крові, а також антиоксидантно-прооксидантного балансу тканини серця, легень і печінки в динаміці гострого періоду, періодів ранніх і пізніх проявів травматичної хвороби (протягом 28 діб) після нанесення політравми. Встановлено, що у посттравматичному періоді спостерігалося збільшення вмісту прозапальних цитокінів. Характерною особливістю динаміки туморнекротичного фактора-α та інтерлейкіну-1b було 2 періоди максимального зростання - через 3 і 21 доби. Антиокисдантно-проокисдантний баланс у тканині серця, легень і печінки у всі терміни спостереження був зміщений в бік переважання прооксидантних механізмів, що характеризувалося так само двома періодами найбільших порушень: через 3 і 21 доби. Отримані результати дозволяють стверджувати, що в динаміці політравми існує відповідність найбільших проявів системної відповіді організму на запалення максимуму інтенсифікації процесів ліпідної пероксидації у внутрішніх органах. Ключові слова: політравма, цитокіни, антиокисдантно-проокисдантний баланс.